Prevalence of sleep disturbances in Chinese university students: a comprehensive meta‐analysis. (31st January 2018) - Li, Lu; Wang, Yuan‐Yuan; Wang, Shi‐Bin; Zhang, Ling; Li, Lin; Xu, Dan‐Dan; Ng, Chee H.; Ungvari, Gabor S.; Cui, Xiling; Liu, Zhao‐Min; De Li, Spencer; Jia, Fu‐Jun; et al.
Summary: This is a meta‐analysis of the pooled prevalence of sleep disturbances and its associated factors in Chinese university students. English (PubMed, PsycINFO, Embase) and Chinese (SinoMed, Wan Fang Database and Chinese National Knowledge Infrastructure) databases were systematically and independently searched from inception until 16 August 2016. The prevalence of sleep disturbances was pooled using random‐effects model. Altogether 76 studies involving 112 939 university students were included. The overall pooled prevalence of sleep disturbances was 25.7% (95% CI: 22.5–28.9%). When using the screening scales Pittsburgh Sleep Quality Index, Athens Insomnia Scale and Self‐Rating Sleeping State Scale, and the diagnostic criteria of the Chinese Classification of Mental Disorders (Second Edition), the pooled prevalence of sleep disturbances was 24.1% (95% CI: 21.0–27.5%) and 18.1% (95% CI: 16.4–20.0%), respectively. The percentages of students dissatisfied with sleep quality and those suffering from insomnia symptoms were 20.3% (95% CI: 13.0–30.3%) and 23.6% (95% CI: 18.9–29.0%), respectively. Subgroup analyses revealed that medical students were more vulnerable to sleep disturbances than other student groups. There was no significant difference between males and females, and across geographic locations. Sleep disturbances are common in Chinese university students. Appropriate strategies for prevention and treatment of sleep disturbances in this population need greater attention.